Mining and Clustering of mobile transaction sequences in location based service environment (International Journal of Engineering and Computer Science, 2014)
The improved capabilities of the recent cellular phones compared to older ones had lead the telephone companies offer a lot of value added services. Emergence of new technologies will lead to emergence of new services increasing the percentage of users for such services. To improve the quality of services provided for the users, mining and clustering of different mobile transaction behavior are useful. For clustering we have LBS based algorithm. LBS based services which are in demand are used to find a location, people, services and to find similarities to predict next behavior of mobile user